2018
DOI: 10.1002/bjs.10837
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in the classification of appendicitis during laparoscopy

Abstract: BackgroundThe intraoperative classification of appendicitis dictates the patient's postoperative management. Prolonged antibiotic prophylaxis is recommended for complex appendicitis (gangrenous, perforated, abscess), whereas preoperative prophylaxis suffices for simple appendicitis. Distinguishing these two conditions can be challenging. The aim of this study was to assess interobserver variability in the classification of appendicitis during laparoscopy.MethodsShort video recordings taken during laparoscopy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
2
19
1
Order By: Relevance
“…In 2018, a survey among Dutch surgeons demonstrated that a clear standard of care is missing both in patient selection and in determining the length of antibiotic treatment following appendectomy. However, the authors assessed the inter-observer variability in the classification of AA during laparoscopy and demonstrated that agreement was minimal for both the classification of AA ( κ score 0.398) and the decision to prescribe postoperative antibiotic treatment ( κ score 0.378) [ 183 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, a survey among Dutch surgeons demonstrated that a clear standard of care is missing both in patient selection and in determining the length of antibiotic treatment following appendectomy. However, the authors assessed the inter-observer variability in the classification of AA during laparoscopy and demonstrated that agreement was minimal for both the classification of AA ( κ score 0.398) and the decision to prescribe postoperative antibiotic treatment ( κ score 0.378) [ 183 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may have introduced bias in the study, but given the complexity of organising and ethical issues in storing patient data from 16 countries, this was not done. Inter-observer error when grading adhesions which limit surgery is rather subjective, and inter-observer variability has been reported in other laparoscopic assessment and grading, with a recent study in appendicitis showing poor reproducibility [ 31 ]. Our study only requested whether an intra-operative complication occurred or not and further descriptors were not requested.…”
Section: Discussionmentioning
confidence: 99%
“…Van den boom et al showed short video recordings taken during laparoscopy for suspected appendicitis to 80 surgeons and surgical residents and found that inter-observer agreement was minimal in the classification of appendicitis and in the choice of postoperative antibiotic regime, with only slight improvement when published criteria were used. 14 We did identify a paediatric study using a classification similar to the one used in our study. Feng et al prospectively collected intra-operative findings on 84 children at a single centre and categorised the degree of peritoneal contamination as 'localised' (confined to the right lower quadrant and pelvis) or 'extensive' (extending to the liver upon initial visualisation).…”
Section: Discussionmentioning
confidence: 99%